Evolution of the Intellectual Property Information System at the Kalimantan Institute of Technology Using the Waterfall Method and Design Thinking - Rajab, Nur Ali; Marianta, Arwin; Lestari , Ika; Azhar, Nur Fajri; Prihasto, Bima (STMIK Widya Cipta Dharma, 2025)
Intellectual Property (IP) Management at the Kalimantan Institute of Technology (ITK) was previously hindered by manual processes using Google Forms and Excel that were inefficient and prone to errors, and by limited information systems. This research aims to evolve the ITK Intellectual Property Information System (SIM KI) to enhance data management efficiency at the backend and improve functionality and user experience at the frontend. The development methodology uses a structured Waterfall approach. The backend is developed with Node.js (Express) and PostgreSQL, while the frontend uses React JS with interface design based on Design Thinking. System verification is conducted comprehensively through Black Box Testing, White Box Testing, User Acceptance Testing (UAT), and the System Usability Scale (SUS). The evolution results show successful system implementation that now supports four types of IP (Copyright, Patent, Trademark, Industrial Design). Backend testing through unit testing validates the reliability of internal logic, while frontend testing demonstrates functional success (Black Box), good usability (SUS score 77.89), and significant user acceptance improvement (UAT score increased from 68% to 76%). The evolution of SIM KI successfully resulted in a more efficient, functional, and well-received digital platform, which implies increased effectiveness of IP management in the academic environment of ITK.